PsycEXTRA Dataset 2012
DOI: 10.1037/e519682015-035
|View full text |Cite
|
Sign up to set email alerts
|

The Multifold Relationship Between Memory and Decision Making: An individual-differences study

Abstract: Several judgment and decision-making tasks are assumed to involve memory functions, but significant knowledge gaps on the memory processes underlying these tasks remain. In a study on 568 adults between 25 to 80 years, hypotheses were tested on the specific relationships between individual differences in working memory, episodic memory, and semantic memory, respectively, and six main components of decision-making competence. In line with the hypotheses, working memory was positively related with the more cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 81 publications
(168 reference statements)
4
33
0
Order By: Relevance
“…We speculate that different mechanisms may explain why older adults are less inclined than younger adults to engage in maximizing, including alternative search (Peters & Bruine de Bruin, 2012; Strough, Parker, & Bruine de Bruin, 2015). First, older adults face cognitive declines that make it harder to correctly implement complex decision rules like maximizing (Bruine de Bruin, Parker, & Fischhoff, 2012; Del Missier, Mäntylä, Hansson, Bruine de Bruin, & Parker, 2013), which contributes to their preferences for smaller choice sets (Liu, Wood,& Hanoch, 2015). Second, the finding that older adults are less likely than younger adults to engage in excessive alternative search may reflect their increased motivation to optimize positive affective experiences (Carstensen, 1992), and their reduced willingness to spend effort on difficult tasks they no longer enjoy (Bruine de Bruin, McNair, Taylor, Summers, & Strough, 2015; Strough, Bruine de Bruin, & Peters, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that different mechanisms may explain why older adults are less inclined than younger adults to engage in maximizing, including alternative search (Peters & Bruine de Bruin, 2012; Strough, Parker, & Bruine de Bruin, 2015). First, older adults face cognitive declines that make it harder to correctly implement complex decision rules like maximizing (Bruine de Bruin, Parker, & Fischhoff, 2012; Del Missier, Mäntylä, Hansson, Bruine de Bruin, & Parker, 2013), which contributes to their preferences for smaller choice sets (Liu, Wood,& Hanoch, 2015). Second, the finding that older adults are less likely than younger adults to engage in excessive alternative search may reflect their increased motivation to optimize positive affective experiences (Carstensen, 1992), and their reduced willingness to spend effort on difficult tasks they no longer enjoy (Bruine de Bruin, McNair, Taylor, Summers, & Strough, 2015; Strough, Bruine de Bruin, & Peters, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that included age-diverse samples found that older adults were better than younger adults at avoiding sunk-cost bias, or cancelling failing plans even when investments were irretrievable (Bruine de Bruin, Parker, & Fischoff, 2012; Bruine de Bruine, Strough, & Parker, 2014; Del Missier, Mäntylä, Hansson, Bruine de Bruin, & Parker, 2013; Strough, Mehta, McFall, & Schuller, 2008). This age-related improvement typically showed little to no associations with age-related changes in fluid and crystallized cognitive abilities, which suggested the importance of non-cognitive factors (see Strough et al, 2015b for a review).…”
Section: Aging and Decisionsmentioning
confidence: 99%
“…For older adults, experience and emotion regulation skills may facilitate the preservation of decision-making competence, even in the face of cognitive declines (Peters & Bruine de Bruin, 2012; Peters, Hess, Vastjfall, & Aumann, 2007; Strough et al, 2011a; Strough et al, 2015b). A growing number of studies have tested this idea (Del Missier et al, 2013; Hess, Osowski, & Leclerc, 2005; Hess et al, 2013; Mikels, Cheung, Cone, & Gilovich, 2012). Emotion regulation was important for understanding why older adults made better decisions about sunk costs (Bruine de Bruin et al, 2014; Strough, Schlosnagle & DiDonato, 2011b).…”
Section: Aging and Decisionsmentioning
confidence: 99%
“…Having good decision-making competence is associated with better life outcomes, even after controlling for socio-economic status and other abilities (Bruine de Bruin, Parker, & Fischhoff, 2007). However, well-documented age-related declines in fluid cognitive ability may threaten the quality of older adults’ decisions (Bruine de Bruin, Parker, & Fischhoff, 2012; DelMissier, Mäntylä, Hansson, Bruine de Bruin, & Parker, in press; Finucane & Gullion, 2010), underscoring the need for identifying other, perhaps non-cognitive, pathways to maintaining decision-making competence across the life span. A better understanding of the skills that contribute to making good decisions should help us to design interventions that teach better decision making to people of all ages, thus improving quality of life across the life span.…”
mentioning
confidence: 99%
“…The few studies that have included age-diverse samples report inconsistent findings about the relationship between aging and decision-making competence, perhaps due to using different types of decision tasks. Indeed, studies using cognitively demanding decision tasks show age-related declines in performance, but studies using cognitively less demanding decision tasks show either no change or improvements with age (Bruine de Bruin et al, 2012; DelMissier et al, in press; Peters & Bruine de Bruin, 2012). This pattern of results is in line with the emerging view that good decisions do not only involve cognitive abilities but also affective or experiential skills (Reyna, 2004; Stanovich & West, 2008), and with speculations that age-related improvements in affective or experiential skills may counteract age-related cognitive declines in decision making (Hess, Queen, & Ennis, 2012; Peters, Hess, Västfjäll, & Auman, 2007; Peters & Bruine de Bruin, 2012; Strough et al, 2011a).…”
mentioning
confidence: 99%